1996
DOI: 10.3928/1081-597x-19960501-09
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Stability of the Cornea After Radial Keratotomy and Photorefractive Keratectomy

Abstract: BACKGROUND: Corneal refractive surgical procedures alter the shape and structure of the tissue, possibly compromising its mechanical stability. METHODS: One or both eyes of 87 subjects were studied: 26 of these 87 had been treated for myopia by excimer laser ablation and 36 by radial keratotomy; 25 without previous corneal surgery functioned as controls. Corneal topography was evaluated by TMS-I videophotokeratography before and after 180° tilting of the patient, and the pressureinduced ring-wise cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“… 14 The human cornea has been found to change curvature in response to IOP increments of 5 mmHg, 8 mmHg, and 16 mmHg. 15 16 17 With limbal integrity being affected during DALK, cylindrical changes might be more pronounced with higher IOP.…”
Section: Discussionmentioning
confidence: 99%
“… 14 The human cornea has been found to change curvature in response to IOP increments of 5 mmHg, 8 mmHg, and 16 mmHg. 15 16 17 With limbal integrity being affected during DALK, cylindrical changes might be more pronounced with higher IOP.…”
Section: Discussionmentioning
confidence: 99%
“…For example, radial keratotomy (RK) stromal incisions which have been used in the past for the correction of myopic refractive errors were associated with significant long-term instability. 6 Böhringer et al 7 evaluated longer-term outcomes of manual astigmatic keratotomy (AK) and found an increase of keratometric astigmatism after the procedure by 0.3 D/year, equalizing the surgical effect after 10 years. The authors concluded that it may be interesting to check whether the use of a femtosecond laser makes FSAK more stable than manual arcuate keratotomy over a longer follow-up time.…”
mentioning
confidence: 99%